THE INFORMAL LEARNING ATMOSPHERE EXPOSED TO AN EFL LEARNER WITH ADHD IN VOCABULARY MASTERY - Suhani, Rizka; Susilawati, Endang; Riyanti, Dwi (Universitas Tanjungpura, 2023)
This study was aimed to identify the components of the informal learning atmosphere exposed to the EFL learner with ADHD who had a surprising capability in vocabulary mastery and to describe the ADHD learner